The HIV epidemic in Eastern Europe and Central Asia. - Dehovitz, Jack; Uuskula, Anneli; El-Bassel, Nabila (Current HIV/AIDS reports, 2014)
Eastern Europe and Central Asia represent one of the few regions globally where there is a continued increase in the incidence of HIV infection. For example, in Eastern Europe the rate of diagnosed cases of HIV infection per 100 000 population has increased from 11.7 in 2004 to 22.5 in 2011. Initially propelled by injection drug use, heterosexual transmission has now become a major driver of new infections in the region. Nonetheless substance use remains an important factor, with its control limited by challenges in scaling up harm reduction efforts. While most countries have implemented opioid substitution therapy programs, their scale remains very limited. Similarly, coverage of needles syringe programs across the region is variable. Complicating the control of HIV has been the emergence of non-injection drugs and inadequate access to antiretroviral therapy. In addition, structural barriers and stigma toward HIV infected people may contribute to the high proportion of late presentations for HIV care. Finally in the wake of the HIV epidemic, high rates of hepatitis C infection and tuberculosis have been noted.
Keywords: Adolescent; Adult; Anti-HIV Agents; Asia; Drug Users; Epidemics; Europe, Eastern; Female; Global Health; Hepatitis C; HIV Infections; Homosexuality, Male; Humans; Incidence; Male; Middle Aged; Needle-Exchange Programs; Prevalence; Sex Workers; Tuberculosis; Young Adult